Penguatan Solidaritas Lintas Daerah Dalam Merajut Harmoni Kebangsaan Bagi Mahasiswa - Sopian Tamrin; Idham Irwansyah; Ashari Ashari; Mario Mario; Riri Amandaria (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2023)
This service aims to strengthen diversity awareness for students, especially those from Bone and Luwu districts in Makassar. This activity has a strong motivation considering the tendency of Bone and Luwu students to be involved in regional conflict cases some time ago. The method used is to provide insight strengthening in the form of discussion. The activity participants came from two student communities, namely Bone students and Luwu students. This activity took place in October 2022 offline at the IPMIBAR secretariat. The material presented includes national worldviews, and students' social and intellectual responsibilities, as well as the role of students in caring for national solidarity. This activity is expected to be a trigger for social and intellectual awareness for regional communities in caring for national solidarity. With this activity the service team also hopes to minimize conflicts that often occur among students